Analisa Kinerja Mesin Load Bank Genset Isuzu Diesel 50 KVA Terhadap Penggunaan Jenis Bahan Bakar Pertamina Dex Dan Biosolar - Yudhi Chandra Dwiaji; Muh Anhar (Politeknik Negeri Samarinda, 2021)
Generator sets are a combination of generators and drive engines combined into one unit to generate electricity. The drive engine in the generator set is generally an internal combustion engine either in the form of a motor / diesel engine with diesel fuel or an engine with gasoline. Some variants of pertamina diesel motorcycles commonly marketed in Indonesia are biosolar and Pertamina Dex. The fuel has a different centane value. The fuel at first glance looks the same, but has unequal characteristics. Comparisons that examined fuel, biosolar and pertamina dex get results if pertamina dex and biosolar have a lower fuel consumption value than diesel. This study will compare the level of fuel consumption and effective power of biosolar fuel with pertamina dex and describe the results, with the aim that Pertamina fuel users have a valid data reference in determining better fuel choices.